Formin-dependent synaptic growth: evidence that Dlar signals via Diaphanous to modulate synaptic actin and dynamic pioneer microtubules. - Pawson, C.; Eaton, B.A.; Davis, G.W. (Journal of Neuroscience, 2008)
The diaphanous gene is the founding member of a family of Diaphanous-related formin proteins (DRFs). We identified diaphanous in a screen for genes that are necessary for the normal growth and stabilization of the Drosophila neuromuscular junction (NMJ). Here, we demonstrate that diaphanous mutations perturb synaptic growth at the NMJ. Diaphanous protein is present both presynaptically and postsynaptically. However, genetic rescue experiments in combination with additional genetic interaction experiments support the conclusion that dia is necessary presynaptically for normal NMJ growth. We then document defects in both the actin and microtubule cytoskeletons in dia mutant nerve terminals. In so doing, we define and characterize a population of dynamic pioneer microtubules within the NMJ that are distinct from the bundled core of microtubules identified by the MAP1b-like protein Futsch. Defects in both synaptic actin and dynamic pioneer microtubules are correlated with impaired synaptic growth in dia mutants. Finally, we present genetic evidence that Dia functions downstream of the presynaptic receptor tyrosine phosphatase Dlar and the Rho-type GEF (guanine nucleotide exchange factor) trio to control NMJ growth. Based on the established function of DRFs as Rho-GTPase-dependent regulators of the cell cytoskeleton, we propose a model in which Diaphanous links receptor tyrosine phosphatase signaling at the plasma membrane to growth-dependent modulation of the synaptic actin and microtubule cytoskeletons.